Global knowledge work : diversity and relational perspectives - Nicolopoulou, Katerina (Edward Elgar Publishing Ltd. CheltenhamGB, 2011)
Aims to capture a snapshot of the evolution of the concept of knowledge work and workers and theoretical and practical implications of this phenomenon.